A functional SrF2 coated separator enabling a robust and dendrite-free solid electrolyte interphase on a lithium metal anode. Issue 37 (6th September 2019) - Li, Xing; Liu, Yang; Pan, Yong; Wang, Mingshan; Chen, Junchen; Xu, Hao; Huang, Yun; Lau, Woon Ming; Shan, Aixian; Zheng, Jianming; Mitlin, David
Abstract : An SrF2 microsphere layer on a separator could be involved in SEI formation and result in a dendrite free SEI on a lithium anode. Abstract : An unstable solid electrolyte interphase (SEI) and accompanying Li metal dendrites are the key impediments to commercialization of high-energy lithium metal batteries (LMBs). We employ a strontium fluoride (SrF2 ) microsphere coated polypropylene (PP) separator to stabilize the SEI and to prevent dendrites from growing. This approach is tested with Li‖Cu half-cells, Li‖Li symmetrical cells, and Li‖NMC full LMBs, there being a major improvement in each case. The Li‖Cu cell with SrF2 maintains a stable coulombic efficiency (CE) of 80% after 100 cycles, when tested at 0.25 mA cm −2 to a capacity of 0.5 mA h cm −2 . By comparison, the uncoated PP reference has a CE of 10% in cycle 60. The Li‖Li cell with SrF2 exhibits a markedly smaller voltage polarization and is able to stably cycle for approximately 340 h vs. the reference which begins to display severe voltage instability at 200 h. The Li‖NMC full LMB with SrF2 shows an initial discharge capacity of 173 mA h g −1, with 167 mA h g −1 (96.5%) being retained after 200 cycles at 200 mA g −1 (1C rate). The SrF2 containing LMB also has a substantially improved rate capability over the reference, the difference being drastic even at the highest testing rate of 20C. First-principles calculations based on DFT indicate that lithium ions prefer to adsorb onto the SrF2 surface, which should create a more uniform ion flux and reduce the propensity for dendrite nucleation. In parallel, the SrF2 spheres bind with the SEI layer, creating a tough in situ formed composite membrane that mechanically stabilizes a planar metal interface.